Evaluation of Long Furrow Field Irrigation in Rahad Agricultural Corporation, Sudan - Mustafa, Julia A.E.; Adeeb, Ali M.; Abdelgalil, Eltigani B. (Gezira Journal of Engineering and Applied Sciences; Vol 18 No 2 (2023), 2026)
Due to the near-depletion of Sudan's shared Nile water resources, expanding irrigated agriculture requires optimizing and implementing water-saving measures within existing irrigation networks. This study monitored and evaluated the performance of a long-furrow surface irrigation system within the Rahad Agricultural Corporation. To ensure repeatability, field data, including inflow rates via siphons, advance recession times at 20-meter stations, and infiltration using the blocked furrow method, were collected from three randomized furrows over six irrigations and analyzed in Excel to compute performance indicators (Ea, Es, DP RO, CU) and water productivity. Observations revealed that the furrows lost their original parabolic shape, becoming deeper at the head and flatter at the tail area. Measured discharges ranged from 3.9 to 5.27 lps, with advance and recession times being significantly longer during the first irrigation due to soil dryness and recent tillage. The application efficiency ranged from 58% to 72% (mean 65%), with the majority of losses occurring as surface runoff (26%-39%, mean 33%). Deep percolation was minimal, averaging less than 2%, which is typical of surface irrigation performance on clay soils. While storage efficiency (86% - 97%) and uniformity coefficients (84% - 94%) remained acceptable, land productivity was only 10% of research potential, resulting in a low water productivity of 0.083 kg/m³. System performance can be enhanced by implementing measures to reduce runoff, such as cutback or surge irrigation, furrow bunds, and tailwater reuse.